(3gjcdI GdCLgRI hUfY GdSjGSGJ hJfajO GdHQGeL GdMchejIs - (3ehab MOjO(B, (3eMeOs ((3YeGf(B:s (3OGQ GdTQhb ddfTQ hGdJhRjY(B,s, 2007)
(3eaghe GdEOGQI GdYGeI hhXGFagG hGdeTGcd GdJj JYGdLgG,eSGgeI GdMVGQGJ aj JWhQ GdacQ GdEOGQj GdMOjK,HjFI GdEOGQI GdYGeI hCKQgG Ydi GdSdhc GdJfXjej,fXQjGJ GdEOGQI GdYGeI,GdYedjI GdEOGQjI hhXGFa GdeOjQ,JUeje GdgjGcd GdJfXjejI GdMchejI,GdbjGOI hGJNGP GdbQGQGJ aj GdCLgRI GdMchejI,JfajP hJbjje GdHQGeL GdMchejI,GdehGRfI GdYGeIs
(3HHdjhZQGajG(B:(3U U(B.269-277s
Keywords: (3GdEOGQI GdYGeIs